The Aryl Hydrocarbon Receptor and Tumor Immunity - Xue, Ping; Fu, Jinrong; Zhou, Yufeng (Frontiers in Immunology, 2018)
The aryl hydrocarbon receptor (AhR) is an important cytosolic, ligand-dependent transcription factor. Emerging evidence suggests the promoting role of the AhR in the initiation, promotion, progression, invasion and metastasis of cancer cells. Studies on various tumor types and tumor cell lines have shown high AhR expression, suggesting that AhR is activated constitutively in tumors and facilitates their growth. Interestingly, immune evasion has been recognized as an emerging hallmark feature of cancer. A connection between the AhR and immune system has been recognized, which has been suggested as an immunosuppressive effector on different types of immune cells. Certain cancers can escape immune recognition via AhR signaling pathways. This review discusses the role of the AhR in tumor immunity and its potential mechanism of action in the tumor microenvironment.